Features of the employment contract with medical and pharmaceutical workers - Olzhabaevna , X.B. (Bulletin of the Karaganda University “Law Series”, 2021)
The basic method in implementation of constitutional law of Kazakhstan citizens for protection of health and medical aid is endowment of medical and pharmaceutical employees of special labor capacity and special le-gal status, generating differentiation in regulation of their labor by regulatory acts. This article reviews pecu-liarities in application of the basic principles of laborlaw — integrity and differentiation with respect to med-ical and pharmaceutical employees. The differentiation of labor of this category of workers is analyzed on such grounds as: industry affiliation, working conditions, the nature of the labor relationship between the em-ployee and the employer, and their content is determined. The critical analysis of some norms of the Labor Code of the Republic of Kazakhstan dated November 23, 2015 and Code of the Republic of Kazakhstan «On health of people and healthcare system» dated July 7, 2020 in terms of regulation of special legal status of re-viewed category of employees allowed to identify the peculiarities of employment contract with medical and pharmaceutical employees, allowing to establish no only rights but also increase duties and responsibility of these employees to preserve life and health of citizens both humanitarian values of human society. The con-clusion made is the peculiarities in content and conclusion of employment contract with pharmaceutical and medical employees are caused by their special legal status. The conclusions are also substantiated by the posi-tions of scientists who have studied the features of labor contracts with these special subjects of labor law. The author made proposal on improvement of domestic labor and medical legislation concerning conditions and procedure for conclusion of employment contracts.